The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/jfb11010009
|View full text |Cite
|
Sign up to set email alerts
|

Myristyltrimethylammonium Bromide (MYTAB) as a Cationic Surface Agent to Inhibit Streptococcus mutans Grown over Dental Resins: An In Vitro Study

Abstract: This in vitro study evaluated the effect of myristyltrimethylammonium bromide (MYTAB) on the physical, chemical, and biological properties of an experimental dental resin. The resin was formulated with dental dimetacrylate monomers and a photoinitiator/co-initiator system. MYTAB was added at 0.5 (G 0.5% ), 1 (G 1% ), and 2 (G 2% ) wt %, and one group remained without MYTAB and was used as the control (G Ctrl ). The resins were analyzed for the polymerization kinetics, degree of conversion, ultimate tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…The antifungal mechanism of DMAHDM is still not clear but is assumed to be led by the interaction between the phospholipid components of the cytoplasmic membrane, and a net positive charge on microbial cells (Jain et al, 2017; Obłąk, Piecuch, Krasowska, & Łuczyński, 2013). Similar to the bacteria, the suggested mechanism is producing membrane distortion as well as ATP, leakage, forcefully disrupting plasma membrane structure, and decreasing the survival of fungal cells (Fait, Bakas, Garrote, Morcelle, & Saparrat, 2019). DMAHDM held a high surface charge density (Li et al, 2014), which has been suggested as a critical factor for determining the antifungal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal mechanism of DMAHDM is still not clear but is assumed to be led by the interaction between the phospholipid components of the cytoplasmic membrane, and a net positive charge on microbial cells (Jain et al, 2017; Obłąk, Piecuch, Krasowska, & Łuczyński, 2013). Similar to the bacteria, the suggested mechanism is producing membrane distortion as well as ATP, leakage, forcefully disrupting plasma membrane structure, and decreasing the survival of fungal cells (Fait, Bakas, Garrote, Morcelle, & Saparrat, 2019). DMAHDM held a high surface charge density (Li et al, 2014), which has been suggested as a critical factor for determining the antifungal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…QACs have been studied due to their high and broad antibacterial spectra, even at small concentrations [25][26][27]. In the case of TAT, it was suggested that the mechanism of antibacterial action is due to "contact killing" effect [6].…”
Section: Discussionmentioning
confidence: 99%
“…The resin infiltrants were tested for ultimate tensile strength (UTS) using ten samples per group [ 29 ]. The samples were prepared in a metallic mold measuring 8.0 mm long, 2.0 mm wide, and 1.0 mm thickness.…”
Section: Methodsmentioning
confidence: 99%